The distance–power consumption trade–off with the optimal number of relays for cooperative Wireless Sensor Networks. (24th February 2012) - Joe, Inwhee; Chung, Sungmoon
Cooperative communication allows achieving the effects of the virtual MIMO, so that diversity gain can be obtained from just one antenna for each node. However, conventional cooperative communication causes lower data rates as diversity gain increases. In addition, increasing the number of relays makes networks consume more power. This is one of the most important issues for cooperative Wireless Sensor Networks (WSNs). Therefore, we propose an appropriate system model to achieve the optimal number of relays in terms of power consumption by studying the trade–off between the distance (from source to destination) and power consumption in consideration of the data rate.